Variations within Toll‐like receptor (TLR) and TLR signaling pathway‐related genes and their synergistic effects on the risk of Guillain‐Barré syndrome. Issue 2 (23rd February 2022) - Dutta, Debprasad; Nagappa, Madhu; Sreekumaran Nair, Binu V.; Das, Sumit Kumar; Wahatule, Rahul; Sinha, Sanjib; Vasanthapuram, Ravi; Taly, Arun B.; Debnath, Monojit
Abstract: Guillain‐Barré syndrome (GBS) is the commonest post‐infectious polyradiculopathy. Although genetic background of the host seems to play an important role in the susceptibility to GBS, genes conferring major risk are not yet known. Dysregulation of Toll‐like receptor (TLR) molecules exacerbates immune‐inflammatory responses and the genetic variations within TLR pathway‐related genes contribute to differential risk to infection. The aim of this study was to delineate the impact of genetic variations within TLR2, TLR3, and TLR4 genes as well as TLR signaling pathway‐related genes such as MyD88, TRIF, TRAF3, TRAF6, IRF3, NFκβ1, and IκBα on risk of developing GBS. Fourteen polymorphisms located within TLR2 (rs3804099, rs111200466), TLR3 (rs3775290, rs3775291), TLR4 (rs1927911, rs11536891), MyD88 (rs7744, rs4988453), TRIF (rs8120), TRAF3 (rs12147254), TRAF6 (rs4755453), IRF3 (rs2304204), NFκβ1 (rs28362491), and IκBα (rs696) genes were genotyped in 150 GBS patients and 150 healthy subjects either by PCR‐RFLP or TaqMan Allelic Discrimination Assay. Genotypes of two polymorphic variants, Del/Del of rs111200466 insertion and deletion (INDEL) polymorphism of TLR2 gene and TT of rs3775290 single nucleotide polymorphism (SNP) of TLR3 gene had significantly higher frequencies among GBS patients, while the frequencies of TT genotype of rs3804099 SNP of TLR2 gene and TT genotype of rs11536891 SNP of TLR4 gene were significantly higher in controls. Gene‐gene interaction study by Multifactor Dimensionality Reduction analysis also suggested a significant combined effect of TLR2, and NFκβ1 genes on the risk of GBS. The SNPs in the IκBα and IRF3 genes correlated with severity of GBS. The genes encoding TLRs and TLR signaling pathway‐related molecules could serve as crucial genetic markers of susceptibility and severity of GBS.